PENGARUH MANFAAT PERSEPSIAN DAN KREDIBILITAS PERSEPSIAN TERHADAP PENGGUNAAN E-BANKING PADA PERUSAHAAN-PERUSAHAAN INDONESIA - Melissa Tri Angela Simarmata; Jadongan Sijabat (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2014)
The purpose of this study is to provide empirical evidence about the influence of perceived benefits (perceived benefits) and perceived credibility (perceived credibility) to the use of e-banking. This study is based on Social Contract Theory and the Theory of Diffusion of Innovations. Samples are intended private companies located in Yogyakarta and gained as much as 71 companies. Statistical analysis is done is test the initial validity and reliability tests early, test construct validity and reliability tests construct instruments, test Classical Assumptions: Normality test, test Multicollinearity, Heteroskidastity test, and autocorrelation test. Multiple Regression Analysis to test the empirical model and hypotheses. The results showed that the perceived benefits of (Perceived Benefits) has a positive effect on the use of e-banking. However, the influence of perceived credibility (Perceived Credibility) against the use of E-Banking (E-Banking Usage) is not proven. Keywords: social contract theory, theory of diffusion of innovations, benefits perceived, perceived credibility and use of e-banking.